Diotic and Antiphasic Digits-in-noise Testing as a Hearing Screening and Triage Tool to Classify Type of Hearing Loss. Issue 3 (17th November 2021) - De Sousa, Karina C.; Smits, Cas; Moore, David R.; Myburgh, Hermanus C.; Swanepoel, De Wet
Abstract : Objectives: The digits-in-noise test (DIN) is a popular self-test measure that has traditionally been used to screen for hearing loss by providing either a pass or refer result. Standard approaches either tested each ear monaurally or used a binaural diotic version where identical digits and noise were presented simultaneously to both ears. Recently, a dichotic, antiphasic version was developed, increasing sensitivity of the DIN to unilateral or asymmetric sensorineural hearing loss (SNHL) and conductive hearing loss (CHL). The purpose of this study was to determine predictors and normative ranges of the antiphasic and diotic DIN and to determine if a combination of diotic and antiphasic DIN could accurately categorize hearing into (1) normal, (2) bilateral SNHL, or (3) unilateral SNHL or CHL. Design: The analytical sample consisted of 489 participants between the ages of 18 and 92 years with varying types, symmetry, and degrees of hearing loss. Degree and type of hearing loss were determined based on standard clinical four-frequency (0.5–4 kHz) pure-tone air and bone conduction threshold averages. The sample consisted of bilateral normal hearing (n = 293), bilateral SNHL (n = 172), unilateral SNHL (n = 42), and CHL (n = 32). All participants (n = 489) first completed an antiphasic DIN (digit stimuli 180° out-of-phase between ears), while 393 of the sample also completed a diotic DIN. Two procedures were assessed for their ability to categorize hearing into one of the three hearing groups. The first used a fixed antiphasic cutoff combined with a cutoff formed by a linear combination of antiphasic and diotic speech recognition threshold (SRT) or binaural intelligibility-level difference. Results: Poorer ear pure-tone average was the strongest predictor of antiphasic DIN score, whereas better ear pure-tone average explained more of the variance in diotic SRT. The antiphasic DIN sensitivity and specificity was 90% and 84%, respectively, for detecting hearing loss, with outstanding area under the receiver operating characteristics values exceeding 0.93 to identify hearing loss in the poorer ear. The first fixed SRT cutoff procedure could categorize 75% of all participants correctly, while the second procedure increased correct categorization to 79%. False negative rates for both procedures were below 10%. Conclusions: A sequential antiphasic and diotic DIN could categorize hearing to a reasonable degree into three groups of (1) normal hearing; (2) bilateral SNHL; and (3) unilateral asymmetric SNHL or CHL. This type of approach could optimize care pathways using remote and contactless testing, by identifying unilateral SNHL and CHL as cases requiring medical referral. In contrast, bilateral SNHL cases could be referred directly to an audiologist, or nontraditional models like OTC hearing aids.